Rapid synergistic thrombolysis of ischemic stroke guided by high-resolution and high-speed photoacoustic cerebrovascular imaging - Mengtao Han; Zhiwei Xue; Mengchen Yu; Nanlin You; Yaguang Ren; Zhiqiang Xu; Zhifeng Wu; Yiming He; Zonghai Sheng; Chengbo Liu; Donghai Wang; Jingqin Chen (Photoacoustics)
Thrombosis is the major cause of ischemic stroke and poses a serious health burden globally. Current thrombolytic strategies, such as systematic administration of recombinant human tissue plasminogen activator (rt-PA), are challenged by limited thrombolysis efficiency due to low targeting ability and a short plasma half-life. Here, we report a rapid synergistic strategy that integrates sonothrombolysis and rt-PA mediated pharmacological thrombolysis to achieve accurate and efficient treatment of ischemic stroke. The strategy (PLPA@PFP) uses a platelet-biomimetic membrane as a carrier to deliver both perfluoropentane (PFP) and rt-PA, prolonging half-life and effectively accumulating at the thrombus within 0.5 hours. Upon exposure to focused ultrasound, PFP-based cavitation effects significantly enhance thrombus breakdown and rt-PA penetration, enabling synergistic sono/pharmacological thrombolysis both in vitro and in vivo. High-resolution photoacoustic (PA) imaging provides direct assessment of vascular reperfusion following therapeutic intervention in a murine model of ischemic stroke, offering important guidance for clinical treatment.